PENDAMPINGAN PEMBUATAN PUPUK KOMPOS KEPADA PETERNAK SAPI DI DESA SUMBERBARU KABUPATEN JEMBER - Holil Nawawi ('Ibadatuna : Jurnal Pengabdian Masyarakat, 2022)
The article describes the assistance in making compost for cattle farmers. The research uses the Participatory Learning and Action (PLA) method. It collected secondary and primary data through direct surveys to Sumberbaru Village, Jember Regency. Based on the research results, Sumberbaru Village, especially Karangbayat Hamlet, has much potential in the livestock sector. This is because most of the population owns cattle, of which, in 387 households, 88% own cows and goats whose dung can be processed into compost. So that it can reduce the cost of agricultural expenditure in household activities; in addition, by utilizing cow dung, it can also overcome problems in the existing environment.